Educators' perspectives about teaching and supporting students with learning difficulties in reading. Issue 3 (November 2022) - Serry, Tanya; Snow, Pamela; Hammond, Lorraine; McLean, Emina; McCormack, Jane
We explored the perspectives of school-based educators located in Victoria, Australia, regarding their support of students who have reading difficulties. An anonymous survey was completed by 523 participants, including educators, educational leaders and Student Support Services staff. Results revealed multiple areas of concern related to their capacity to work on reading intervention with these students. Although participants reported that students with reading difficulties were present in most classes, confidence to work effectively with these students was mixed. They described feeling poorly prepared by preservice programs and indicated that insufficient time and mentorship prevented them from serving these students optimally. As a group, they privileged many approaches that align with best practice for struggling readers, such as explicit instruction, but perceived that such practices are not always feasible to implement. Support was also strong for practices considered non-evidence-based, such as adhering to students' preferred 'learning-style'. Recommendations for school-based practice, with a specific focus on students with reading difficulties, are made.